WORKLOAD AND BURNOUT ON PERFORMANCE USING MOTIVATION MEDIATED IN THE NUTRITION INSTALLATION OF RSJD DR RM SOEDJARWADI PROVINCE CENTRAL JAVA - Guntoro, Guntoro; Sudarwati, Sudarwati; Istiatin, Istiatin (STIE PENA, 2024)
This study aims to test and analyze the effect of workload and burnout on employee performance, the effect of workload and burnout on employee motivation and the effect of employee motivation on employee performance in the Nutrition Installation of RSJD Dr. RM. Soedjarwadi, Central Java Province. The method of this research is quantitative descriptive. The number of research respondents was 36, which was determined by the total sampling technique. The results of the study showed that workload had a positive and significant effect on employee motivation (p value 0.000), employee workload had a positive and significant effect on employee performance (p value 0.000), burnout had no effect on employee motivation (p value 0.269), employee burnout had no effect on employee performance (p value 0.284) and employee motivation had no effect on employee performance (p value 0.995). The suggestion of this research is that hospitals should support occupational safety and health, especially nutrition installation officers in informal workplaces through surveys and counseling while working for workers. Keywords: workload, burnout, performance, motivation